Impacts of Land Use Types and Soil Depth on Soil Fertility Status in Dende Kebele, West Gojjam Zone, Ethiopia - Dilnesa Bayle (International Journal of Forestry Research)
Land use change and soil depth lead to subsequent changes in soil physicochemical properties in the northern highlands of Ethiopia. These changes in soil properties indicate a shift in soil fertility levels. The purpose of this study was to examine the impacts of different land use types and soil depths on soil fertility status in Dende Kebele, West Gojjam Zone, Ethiopia. The study utilized a randomized complete block design (RCBD) experimental design, with various land use categories serving as treatments. The study area was purposefully divided into three land use types (Eucalyptus plantation, grazing, and cropped land) and two soil layers (0–20 and 20–40 cm) with three replications. A total of 18 composite soil samples were collected for laboratory analysis. The interaction between land use types and soil depth had a significant impact (p<0.001) on particle size distribution, field capacity (FC), permanent wilting point (PWP), pH, organic carbon (OC), and exchangeable (K+ and Na+) and available micronutrients. The soil texture within the study area was classified as clay. The soil had low to medium bulk density (BD), very high total porosity (TP) and medium available water holding capacity (AWHC). The pH ranged from strongly to moderately acidic with low to medium levels of OC and TN. Available phosphorus (AP) was extremely low, while exchangeable Mg+2 and Ca+2 were high, and Na+ was low to medium. Levels of Fe, Mn, and Zn were high, while Cu levels were low to medium. Overall, the findings suggest that soil fertility was higher in Eucalyptus plantation soils compared to cropped land, highlighting the importance of soil fertility management for sustainable agriculture in the area.